(untitled) (Italian Journal of Public Health, 2011)
Background: Verocytotoxin Escherichia coli is a frequent and important cause of diarrhea and haemolytic uremic syndrome all over the world. Consumption of ground beef, lettuce, and other kinds of food have been associated with outbreaks, The aim of this study was to detect the presence of E. coli O157 in meat products collected from hospital food catering services in Rome, using a rapid detection method in comparison with a standard culture method to verify the effectiveness of HACCP system. Methods: Three hundred and ten food samples (80 of cooked and 230 of raw meat) were screened for E.coli O157 by ISO culture method and by enzyme-linked-fluorescent-assay (ELFA)-based methods (VIDAS® system, bioMérieux). All isolates obtained were tested for VT1 and VT2 genes by PCR. The statistical analysis considered absolute frequencies and percentages. The K statistic was applied to assess agreement between direct culture method and the VIDAS system. Results: A total of 6 (1,9%) E.coli O157 isolates were recovered from raw meat samples by the culture method; of these only four were identified by PCR as VTEC producers. A total of 9 (2,9%) E.coli O157 isolates were recovered from raw meat samples by the VIDAS® system. No E.coli O157 was detected in cooked products. All comparisons between the direct culture method and the VIDAS system were statistically significant (K= 0,795; p<0.001). Conclusions: The present study showed how ELFA-based methods are highly specific and rapid for the detection of E.coli O157 in food samples compared with the direct culture method. ELFA method is useful to verify the effectiveness of the HACCP system in the risk management of potential contaminating hazards during the preparation of foods for susceptible persons